2009
DOI: 10.1007/s10886-009-9706-5
|View full text |Cite
|
Sign up to set email alerts
|

Blue Color Formation of Cyanobacteria with β-Cyclocitral

Abstract: Volatile compounds, such as beta-cyclocitral, geosmin, and 2-methylisoborneol, from cyanobacteria showed a lytic activity against cyanobacteria. Particularly, beta-cyclocitral caused an interesting color change in the culture broth from green to blue during the lysis process. In the present study, the lytic behavior of various cyanobacteria with beta-cyclocitral was investigated, and a mechanism for the blue color formation was developed. beta-Cyclocitral lysed both the laboratory strains of any genera and blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 14 publications
4
25
0
1
Order By: Relevance
“…The concentrations measured at the lysing point were lower than those from the laboratory experiments performed by Ozaki et al (14) and Harada et al (15). However, ␤-cyclocitral, whose pH-dependent distribution coefficient (log D) is 3.3, is hydrophobic; consequently, only 1/2,000 of the added ␤-cyclocitral dissolves in water and shows lytic activity (23).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…The concentrations measured at the lysing point were lower than those from the laboratory experiments performed by Ozaki et al (14) and Harada et al (15). However, ␤-cyclocitral, whose pH-dependent distribution coefficient (log D) is 3.3, is hydrophobic; consequently, only 1/2,000 of the added ␤-cyclocitral dissolves in water and shows lytic activity (23).…”
Section: Discussionmentioning
confidence: 76%
“…Some of these volatile compounds from the cyanobacteria showed lytic activity against the cyanobacteria (14). In particular, ␤-cyclocitral caused an interesting color change in the culture broth from green to blue during the lysis process (14,15). When ␤-cyclocitral was added to the laboratory strains of any genera and to bloom samples, including many species of cyanobacteria, it caused the characteristic result, so that the absorption maxima of chlorophyll a and ␤-carotene disappeared but that of phycocyanin remained for 12 h. This indicated that the oxidation of ␤-cyclocitral leads to acidification, which then preferentially decomposes chlorophyll a and ␤-carotene rather than phycocyanin, so that the inherent color from the tolerant watersoluble pigments became observable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These phenomena might account for that the death and decay of cyanobacteria blooms is often associated with high concentrations of VOSCs. β-Cyclocitral is considered to be the main off-flavor from cyanobacteria (Harada et al, 2009;Li et al, 2007;Yang et al, 2008), which is released during the growth of Microcystis and the disruption of cell integrity (Zhang et al, 2010b). It looks likely that the production of β-cyclocitral is related to metabolism of M. aeruginosa and bacterium (P. pseudoalcaligenes in our study) is not the origin of β-cyclocitral.…”
Section: Results Of Off-flavorsmentioning
confidence: 73%